Kajian Penerapan Hukum Pidana Guna Penyelesaian Konflik Kelompok Buruh di Padang Bai Bali - Ida Bagus Bayu Brahmantya (Fakultas Hukum, Universitas Warmadewa, 2021)
Workers at the Padang Bai port are workers who work daily at the Padang Bai port in Bali serving loading and unloading goods to NTB and NTT. Labor disputes often occur vertically and horizontally, vertically, generally relating to work agreements, while horizontally, namely disputes between groups of workers. This can be a serious problem and has far-reaching effects. This impact eventually forms a conflict. In terms of its relationship, labor conflicts are not only limited to civil law, but labor law can also be reviewed criminally. This can be seen with the issuance of the policy of Law No.13 of 2003 concerning employment, and Law No. 02 of 2004 concerning the settlement of disputes with labor and industry can be subject to criminal law sanctions. It is necessary to note that the development of Padang Bai Port in Bali with the existence of a state-owned company will have a full relationship with the availability of services for these freelance workers. So that when there is a vertical conflict, the criminal law regulates the accountability of labor as a corporation and ensures that laborers have guaranteed legal protection. One other correlation that is the focus of this research is that an action in the field can potentially lead to clashes between groups of workers and lead to criminal action or horizontal disputes. The relevance of this research is to examine the application of criminal law to resolve conflicts vertically and horizontally at ports from the labor side.